The optimal order configuration of turbines in a small hydropower plant: A case study of the Lepenci River in Kosovo - Arlinda Bresa; Bedri Dragusha; Xhevat Berisha; Rexhep Selimaj (Institute of Advanced Engineering and Science, 2022)
Decentralized electricity production from small hydropower plants used for domestic and ancillary services has been established among the most reliable renewable energy sources for isolated locations. However, many factors impact the energy efficiency and the production capacity of such hydropower plants, one of these factors being the order configuration of the connected turbines. Hence, this research presents a performance evaluation of a small hydropower plant consisting of three francis turbines, and it elicits the optimal order configuration of the connected operating turbines, that yields the highest power output under varying conditions. Three scenarios with different order configurations of turbines are presented and compared in a “run-of-the-river” setting, installed in the Lepenci River, in south-eastern Kosovo. Numerical analyses are used to evaluate the performance of each scenario. The results show that the order configuration of the operating turbines based on their connection order has a significant impact on the electricity production.